Multimethodological Framework in the Development of Traceability Systems for Food Supply Chains - Ivan Gunawan (Universitas Muhammadiyah Sidoarjo, 2021)
Food traceability has an important role in maintaining the sustainability of the food supply chain. Every player in a food supply chain must be able to create an internal and external traceability so that the chain traceability can be formed. However, building a suitable food traceability system is not an easy task. The development of a food traceability system has been identified as a complex problem due to the difficulty of accommodating the varied characteristics of each stage in the food supply chain and the interdependence between stages in the food supply chain. Therefore, to solve these complex problems a multimethodology approach is proposed. The multimethodology approach is believed to be able to solve complex multidimensional problems. This article describes a framework for multimethodology in the development of a food traceability system that involves the integration of the Decision Making Trial and Evaluation Laboratory and Interpretive Structural Modeling (DEMATEL-ISM) and System Dynamics (SD). The vegetable oil industry which manages its products in bulk is an interesting case study for the development of a food traceability system because the upstream is in the commodity focused chain and the downstream is in the consumer driven value chain. Ultimately, the multi-methodological framework proved effective in answering the research question of